Women participation on the boards of Malaysian companies and firm performance - Ku Ismail, Ku Nor Izah; Abdullah, Shamsul Nahar (2011)
This study examines the level of women participation on the boards of Malaysian listed companies, and examines the association between women participation on the board and firm performance. We use normalized Tobin’s q and return on assets (ROA) to measure firm performance. An analysis of 841 companies in 2008 shows that 362 (43 percent) of the boards are represented by women, a majority of which are represented by only one woman. On average, women occupy only 7.72 percent of the board seats. This study also shows that a majority of the female directors belong to the Chinese ethnic group, younger than their male counterparts, have one to five years of director experience, and are non-independent directors. Results on the association between women participation on the boards and firm performance are mixed. Using normalized Tobin’s q as a measure of performance, we find that firms with women directors perform poorer than those without women, at a 10 percent significant level. On the other hand, when the ROA is employed, firms with women on boards perform better than those without women, at a 10 percent significant level. This result is consistent with the hypothesis that women representation on the boards of companies is positively associated with company performance. The findings of this study may provide input to the authority responsible for promoting women to become company directors.